2010
DOI: 10.1540/jsmr.46.125
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of direct smooth muscle relaxant effects of the fibrate gemfibrozil

Abstract: Fibrates are commonly employed to treat abnormal lipid metabolism via their unique ability to stimulate peroxisome proliferator-activated receptor alpha (PPARα). Interestingly, they also decrease systemic arterial pressure, despite recent evidence that PPARα may contribute to expression of renin and related hypertension. Yet, mechanisms responsible for their potential antihypertensive activity remain unresolved. Rapid decreases in arterial pressure following bolus intravenous injections of bezafibrate strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Accordingly, proximal and distal segments of each vessel were isolated (Fig. 1), cleaned and carefully sectioned into multiple 3-mm cylindrical rings using a bound set of evenly-spaced scalpel blades as we have successfully employed previously (20,21,22,23). As described in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, proximal and distal segments of each vessel were isolated (Fig. 1), cleaned and carefully sectioned into multiple 3-mm cylindrical rings using a bound set of evenly-spaced scalpel blades as we have successfully employed previously (20,21,22,23). As described in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1, a maximum of eight rings were selected at random from the middle portion of each segment for experimental treatments during each experimental period. Each ring was mounted between two tungsten wire stirrups, which in our experience (20,21,22,23, 25) are strong enough not to bend during ring contractions yet thin enough not to damage the inner endothelial cell layer [presence of intact endothelium was confirmed by relaxation responses to acetylcholine in a representative number of precontracted rings in preliminary and follow-up experiments]. Each ring was then suspended in a 40 ml tissue bath and allowed to equilibrate for several minutes before experimentation at a passive loading (resting) tension of 1,500 mg in standard physiological (Krebs) buffer which was warmed to 37 °C and gassed to pH 7.4 with regulated delivery of O 2 /CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma was stored for later analysis of cholesterol as described below. Then the chest of each animal was opened, lungs and large veins discarded, residual blood in its cavity flushed out with cold physiological buffer, prepared as described previously [45], and the thoracic aorta removed with as much care as possible to minimize stretching. Unfortunately, some stretching was unavoidable as we found that the aorta in this animal was surrounded by considerably more connective and fat tissue than we have encountered in larger species [46].…”
Section: Methodsmentioning
confidence: 99%
“…Each cleaned aorta was then sectioned into a pair of 3-millimeter cylindrical rings, using a bound set of evenly-spaced scalpel blades to optimize length uniformity. Each of these rings was mounted between two tungsten wire stirrups, which are strong enough not to bend during ring contraction yet thin enough not to damage the inner monolayer of endothelial cells [45, 47]. For a select number of aortas, this inner endothelial cell layer was deliberately removed from one ring of each pair (before mounting on stirrups) by rubbing it off with a roughened hypodermic needle inserted through the lumen of the vessel as described previously [47].…”
Section: Methodsmentioning
confidence: 99%